2021
DOI: 10.1097/hs9.0000000000000636
|View full text |Cite
|
Sign up to set email alerts
|

The mTOR Inhibitor Temsirolimus Added to Rituximab Combined With Dexamethasone, Cytarabine, and Cisplatinum (R-DHAP) for the Treatment of Patients With Relapsed or Refractory DLBCL – Results From the Phase-II STORM Trial

Abstract: There is a high need for novel treatment options in relapsed and refractory diffuse large B-cell lymphoma. Single agent mammalian target of rapamycin (mTOR) inhibitor treatment has shown promising efficacy in this entity. Here, we report on the results of the mTOR-inhibitor temsirolimus combined to standard rituximab-DHAP salvage regimen in a prospective, multicenter, phase II, open-label study. The STORM regimen consisted of rituximab 375 mg/m 2 (day 2) and DHAP (dexamethasone 40 mg day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…A phase 3 study AUGUMENT confirmed the benefit of the addition of the immunomodulatory drug lenalidomide to the rituximab in r/r FL and MZL ( 45 ). Strategies involving the addition of mTOR inhibitors to rituximab combined with classic chemotherapeutics are also under investigation for the treatment of patients with r/r DLBCL, with promising results from phase 1 and 2 trials ( 46 , 47 ).…”
Section: Anti-cd20 Mabs and Immunoconjugatesmentioning
confidence: 99%
See 1 more Smart Citation
“…A phase 3 study AUGUMENT confirmed the benefit of the addition of the immunomodulatory drug lenalidomide to the rituximab in r/r FL and MZL ( 45 ). Strategies involving the addition of mTOR inhibitors to rituximab combined with classic chemotherapeutics are also under investigation for the treatment of patients with r/r DLBCL, with promising results from phase 1 and 2 trials ( 46 , 47 ).…”
Section: Anti-cd20 Mabs and Immunoconjugatesmentioning
confidence: 99%
“…Several clinical trials have investigated the efficacy of other combination therapies involving CD20-targeting in patients with B-NHLs. Among these trials, the combination of R-DHAP regimen with temsirolimus, an mTOR inhibitor, has shown encouraging results, demonstrating improved outcomes in patients with r/r DLBCL ( 47 ). Temsirolimus has also demonstrated effectiveness in combination with rituximab alone in patients with r/r MCL in phase 2 clinical trial ( 177 ).…”
Section: Combination Therapies With Cd20 Immunotherapeuticsmentioning
confidence: 99%
“…However, vistusertib did not confer an advantage over mTORC1 inhibitors. The STORM study evaluated the safety and activity of temsirolimus plus R-DHAP as salvage therapy for patients with R/R DLBCL [ 166 ]. This treatment was well tolerated, and the most common AEs were leukopenia (75%), thrombocytopenia (83%), anemia (57%), and hypokalemia (25%) [ 166 ].…”
Section: Introductionmentioning
confidence: 99%
“…The STORM study evaluated the safety and activity of temsirolimus plus R-DHAP as salvage therapy for patients with R/R DLBCL [ 166 ]. This treatment was well tolerated, and the most common AEs were leukopenia (75%), thrombocytopenia (83%), anemia (57%), and hypokalemia (25%) [ 166 ]. At the end of the last follow-up, The ORR after the last cycle was 72% (36/50) with 42% (12/50) of CR.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation